A Method of Plasma Quenching in the Gun Barrel. Issue 5 (January 2021) - Luo, Tian-Fang
Abstract: In order to extend the service life of the barrel and improve its corrosion resistance and wear resistance, plasma quenching technology successfully processed the inner hole material. The treatment effect is obtained by making the analysis of the microstructure, hardness and tribological properties. The results show that the plasma quenching of the barrel material can form a martensitic hardening layer on the surface, when the surface hardness is increased by 725 HV, and the surface abrasion resistance is enhanced by 10 times. This technology provides a new way to extend the life of the barrel.